PENGARUH PENGGUNAAN MEDIA SOSIAL DAN GAYA HIDUP HEDONISME TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA FEB DI UNIVERSITAS NEGERI SURABAYA - Vania Amelia; Tisaul Jannah; Eklesia Dewi Intani; Dwi Yuli Rakhmawati; Angga Martha Mahendra (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This investigation examines how the use of social media and hedonism lifestyle affects consumptive behavior which is the goal of the study. This type of study is quantitative which is obtained from primary data through distributing questionnaires. With the sample used in the study totaling 119 respondents. The data collection method used is random sampling. The IBM Statistics 27 program is used to produce multiple linear regression data analysis results. The findings showed that the utilize of social media has a significant effect on consumptive behavior, as well as the hedonism lifestyle. The findings provide important implications for education in managing consumption patterns more wisely in the digital era.